Framing the End: Analyzing Media and Meaning Making During Cape Town's Day Zero - Voci, Denise; Bruns, Catherine J.; Lemke, Stella; Weder, Franzisca (Frontiers in Communication, 2020)
In this paper, we analyze public discourses in 2018 about water-scarce Cape Town, SA. We investigated the discursive implications of apocalyptic rhetoric such as “Day Zero” by analyzing local and international news media talk (n=111 newspaper articles) surrounding the Cape Town water crisis during pre-, height of and post-crisis moments, complemented by 12 narrative problem-centered interviews in the height of the water crisis. The analysis led to a focus on the relationship between environmental and communicative developments with a high local impact, and mainly on examples of local engagement, social movements or resistance as response to changing environmental scenarios and the evaluation of the role of (news) media in raising community concern and commitment. The findings show that the communication around the (twice-postponed) “Day Zero” in Cape Town is a very fruitful example of the digital disrupted, post-truth communication that happens with environmental issues today.